Legal Aspects of Copyright on Book Photocopying Business Activities - Debora, Debora; Siallagan, Haposan; Nainggolan, Jesella Ramayanti (IHSA Institute, 2024)
Photocopied books are sold at much cheaper prices than original books. These pirated books are very popular with college students because of their affordable prices without thinking about the authenticity of the book. Books are objects of Copyright which are protected by law, therefore the author of the book as the creator and/or holder of Copyright for the work of the book has exclusive rights, namely the right to monopolize his creation in an effort to protect his creation from other parties, such as the right to publish and multiplying his creations or giving permission to other parties to gain economic benefits. Even though copyright is an individual right, there are certain limits regarding public authority to provide access to information for society at large. This article examines how copyright is limited in duplicating books for educational purposes and how UUHC enforces book duplication without the author's permission. The method used to study this problem is the normative research method. Based on the results of the study, it can be concluded. Copyright restrictions can be made as long as they do not conflict with morals, religion, public order, decency, national defense and security. The Copyright Law contains restrictions on Copyright related to education as stated in Article 44 jo. Article 86 wherein stating the specified source, or the obligation of the copyright holder concerned to give permission to another party to translate and/or reproduce the work or can also appoint another party to carry out the translation/reproduction of the work. This is done for creations in the fields of education and research. Law enforcement regarding Copyright violations can be resolved through civil dispute resolution and criminal prosecution